Government-sponsored natural disaster insurance pools: A view from down-under. (March 2016) - McAneney, John; McAneney, Delphine; Musulin, Rade; Walker, George; Crompton, Ryan
Abstract: In the light of the rising cost of natural disasters we review the provision of catastrophe insurance by the public sector in the US, France, New Zealand, Spain, the United Kingdom, and its absence in the Netherlands, where flood risk is viewed as a national security concern. We do this in the context of the Australian home insurance market where insurers increasingly employ risk-reflective, multi-peril premiums as new technology allows them to better understand their exposure to risk. Motivations behind government pools vary by country, as do hazard profiles. In the US, for example, pools have usually arisen in the face of market failure of private sector insurance following a significant natural disaster; the initial concern has been the provision of affordable insurance rather than disaster risk reduction. Government pools have certain advantages over the private sector including their ability to raise funds post-event, but face financial unsustainability given political intervention to maintain affordability of cover in high-risk areas. In Australia, it is too early to judge whether risk-based premiums are leading to better land-use planning and increased mitigation spending, but in the case of northern Australia, a region that faces flooding and tropical cyclone risks, rising premiums are causing concern in Government. Nonetheless, the corollary seems self-evident, i.e. in the absence of transparency about the cost of risk, there is no incentive on the part of homeowners, local councils or land developers to improve the 'riskscape'; insurers are the only actors with immediate financial incentives to acknowledge these risks.